Factos e cousas nas crônicas da revista mato-grossense A Violeta (1916-1937) - Costa, Laís Dias Souza da (2014)
The magazine A Violeta appeared in 1916, in Cuiabá, capital of Mato Grosso, deriving of the Literary Bosom “Júlia Lopes” and was one of the most useful magazines of the state and of Brazil.The magazine circulated since 1916 up to 1950, approximately, and was configured as a meaningful vehicle of divulgation about feminine and feminist causes. The column "Chronica" was published during the 34 years that the magazine circulated and registered a lot of events of the cuiabana and mato-grossense society, which helps us to understand many facets of the History.